Key To a Successful Leadership of Tony Fernandes in Airasia - Badzlina Monica Fitriyana; Belton Sihotang; Cesario Iriansyah Danang Fajar Pamungkas; Sari Wahyuni (Business Review and Case Studies, 2022)
AirAsia is one of the major airlines in Malaysia, which has also become one of the airlines that has successfully adopted the low-cost carrier (LCC) strategy so that it has become a reckoned airline in Southeast Asia. AirAsia's success was initiated by Tony Fernandes with his leadership style. The purpose of this analysis is to identify Tony Fernandes' values and culture, business strategy, leadership type, and leadership traits at AirAsia. Based on qualitative study, it was reveal that Tony Fernandes has the innovation and entrepreneurial skills in the transformation of the airline company and has succeeded in moving his employees to achieve the same goals. Tony applied a leadership style with several approaches, namely Democratic, Charismatic & Servant Leadership in leading at AirAsia. In developing AirAsia's transparent and open organizational values and culture, Tony has demonstrated the characteristics of stewardship and building community. He applies a walk-the-talk and employee-oriented approach that shows listening and persuasion characteristics as well as the characteristics of commitment to the growth of people to create a comfortable working environment and atmosphere in his daily life. In the face of a crisis or challenge, Tony comes down directly to assist his employees to face them, which also shows empathy and healing characteristics. Keywords: tony fernandes, airasia, leadership, success, democratic leader, charismatic leader, servant leadership